Development of a Virtual Tissue Culture Laboratory to Improve the Cognitive Abilities of Vocational School Students Studying Plant Agribusiness - Cholifah, Ayu; Widjanarko, Dwi; Anis, Samsudin (Journal of Vocational and Career Education, 2025)
The problem that arises during tissue culture learning is the limited laboratory facilities. The imbalance between the amount of equipment and the number of students causes the practicum to be carried out in turns for a long time, and is less efficient. The impact is that most students, after being assessed, obtain scores that are not as expected. Due to these problems, efforts are needed to utilize multimedia in virtual laboratories. This study aims to develop a virtual tissue culture laboratory at the Agribusiness Plant and Horticulture Vocational School and analyze the feasibility and effectiveness of the virtual tissue culture laboratory at the Agribusiness Plant and Horticulture Vocational School. This study uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The experimental method used is a one-group pre-test-post-test design, with the selected sample being the XI ATPH class, which has 36 students in the experimental class and 36 students as instrument testing subjects. The results showed that the virtual laboratory was categorized as feasible for tissue culture learning based on assessments by media and material experts. The virtual laboratory was also considered very practical for tissue culture learning. Based on the N-Gain Score calculation, the virtual laboratory improved tissue culture learning outcomes with a high category. This study concludes that the virtual laboratory can overcome the problem of limited practical facilities.